2002
DOI: 10.1002/1521-3951(200202)229:3<1335::aid-pssb1335>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Study of the Lattice Distortions Induced by Aliovalent Pb2+ Impurities in Alkali Halides

Abstract: An embedded cluster analysis of the lattice distortions induced by a Pb 2þ substitutional impurity in NaI, RbI and CsF crystals is presented. Active clusters containing more than 100 atoms and embedded in a quantum representation of the crystalline environment are used. Charge compensation is achieved by introducing a cation vacancy in the host lattice. Both nearest-neighbor (NN) and next-nearest-neighbor (NNN) vacancy positions are explicitly considered, as well as the case where vacancy and impurity are well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…13,54 We have calculated the formation-energy difference between NN and NNN defect configurations and have found that the NN configuration is more stable in all three cases by an amount (0.51 eV) that is quite independent of the specific impurity. We already found in the case of doubly charged aliovalent impurities 28 that purely electrostatic effects are more important in determining distortions and relative stabilities than are overlap repulsive terms (associated with the size mismatch effect). From the discussion of the distortions shown above, it is clear that this is even more the case when the substituted cation is triply charged.…”
Section: Discussion Of the Relative Stabilities Of Nn And Nnn Defect ...mentioning
confidence: 96%
See 2 more Smart Citations
“…13,54 We have calculated the formation-energy difference between NN and NNN defect configurations and have found that the NN configuration is more stable in all three cases by an amount (0.51 eV) that is quite independent of the specific impurity. We already found in the case of doubly charged aliovalent impurities 28 that purely electrostatic effects are more important in determining distortions and relative stabilities than are overlap repulsive terms (associated with the size mismatch effect). From the discussion of the distortions shown above, it is clear that this is even more the case when the substituted cation is triply charged.…”
Section: Discussion Of the Relative Stabilities Of Nn And Nnn Defect ...mentioning
confidence: 96%
“…This situation is different from the case of doubly charged substitutional impurities, which try to approach the electrostatic field of the only neighboring vacancy. 28 The presence of two vacancies, allocated symmetrically with respect to the impurity, prevents this approach from happening, which might well be the reason that the optical properties seem to be less affected by the vacancy effect in the case of triply charged impurities than in the case of doubly charged impurities. 34 Another technical comment may be in order here.…”
Section: Discussion Of the Relative Stabilities Of Nn And Nnn Defect ...mentioning
confidence: 99%
See 1 more Smart Citation